Nursing training on the administration of medication in pediatrics: an assessment of observed and self-reported behavior - Ires Lopes Custódio; Francisca Elisângela Teixeira Lima; Lívia Maia Pascoal; Lorena Pinheiro Barbosa; Patricia Neyva da Costa Pinheiro; Islene Victor Barbosa; Paulo César Almeida
ABSTRACT Objectives: to evaluate the effect of a training program on the administration of intravenous drugs in pediatric patients on the observed and self-reported behavior of the nursing team. Methods: evaluation study carried out with 38 professionals during three phases: Assessment of the behavior observed in the actions performed before training; Training implementation; and Assessment of observed and self-reported behaviors (immediately and six months after training). Results: in the observed behavior, there was an improvement in six (6/12) hand hygiene actions; five (5/14) pertaining to environment Organization, selection, and preparation of materials; and in seven (7/10) referring to the Orientation of the procedure, administration and monitoring of the patient's reactions. In self-reported behavior, there was an improvement in two (2/8) actions. Conclusions: the training resulted in an improvement in the actions of nursing professionals related to the administration of intravenous medications, both in observed and in self-reported behavior.